The Th/U ratio in minerals by a fission-track technique: Application to some reference samples in order to estimate the influence of Th in fission-track dating - Iunes, P. J.; Bigazzi, G.; Hadler N, J. C.; Tello S, C.; Guedes O, S.; Paulo, S. R.; Balestrieri, M. L.; Norelli, P.; Oddone, M.; Osorio A, A. M.; Zuñiga, A. (Elsevier, 2002)
In this work, a recent technique for the determination of the Th/U ratio in minerals and glasses was applied to relevant samples used as reference in fission-track (FT) dating. This technique, developed for estimating the influence of tracks due to the induced fission of thorium in the irradiation with neutron used in the FT dating routine, proved to be adequate for this purpose. One of the age standard used for FT dating, the Durango apatite, yielded a very high Th/U ratio (around 30). Only in case of such a high Th/U ratios did the technique used in this work yield a Th/U value with acceptable precision. For the other studied samples - glasses Macusanite, Moldavite and JAS-G1 - which have Th/U ratios < 5, the experimental error of the Th/U measurement is very high. However, in these cases the contribution of the Th fission to the population of induced tracks is also negligible. For its large Th/U ratio the Durango apatite may introduce systematic errors in FT dating, unless irradiation facilities with high thermalization are used. © 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Durango apatite; Fission-track dating; Th thin film; Th/U ratio; U thin film